Quality Improvement Opportunities in Caring for Patients with Nonepileptic Seizures. (9th September 2014) - Chen, Jasper J.; Thakur, Devendra S.; Bujarski, Krzysztof A.; Jobst, Barbara C.; Kobylarz, Erik J.; Thadani, Vijay M.
Abstract : Background . Patients with nonepileptic seizures (NES) are challenging to treat for myriad reasons. Often patients may be misdiagnosed with having epilepsy and then may suffer unintended consequences of treatment side effects with antiepileptic medication. In addition, patients may be maligned by health care providers due to a lack of ownership by both psychiatrists and neurologists and a dearth of dedicated professionals who are able to effectively treat and reduce severity and frequency of symptoms. Aims of Case Report . Many psychiatrists and neurologists are unaware of the extent of the barriers to care faced by patients with NES (PWNES) and the degree of perception of maltreatment or lack of therapeutic alliance at various stages of their care, including medical workup, video-EEG monitoring, and follow-up plans. We present the case of a patient with NES who experienced numerous barriers as well as incoordination to her care despite being offered a breadth of resources and discuss the quality improvement opportunities that may exist to improve care of patients with NES. Conclusion . No known literature has documented the extensive barriers to care of PWNES in parallel to quality improvement opportunities for improving their care. We endeavor to contribute to the overall formulation and development of a clinical care pathway for PWNES.